1968
DOI: 10.1126/science.161.3844.898
|View full text |Cite
|
Sign up to set email alerts
|

Rete Mirabile of Dolphin: Its Pressure-Damping Effect on Cerebral Circulation

Abstract: In the bottlenose dolphin Tursiops truncatus, a massive retial complex is interposed between the systemic and cerebral circulations at the cervicothoracic level. Pressure measurements in the retial efferent arteries supplying the brain revealed relatively nonpulsatile pressure profiles. These measurements in the anesthetized dolphin demonstrate the pressure-damping effect of the retia mirabile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

1969
1969
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 7 publications
0
30
0
2
Order By: Relevance
“…Moreover, NO, located in sympathetic nerves, can be released as a co-transmitter in the peripheral autonomic system and induces vasodilator effects (Toda and Okamura, 2003). It is well known that Cetaceans have morphophysiological features that permit them to live in aquatic environment (Nagel et al, 1968;Vogl and Fisher, 1981;Ochrymowych and Lambertsen, 1984;Melnikov, 1997;Bombardi et al, 2010Bombardi et al, , 2011. In particular, during diving, blood is shifted to the huge retia mirabilia, to allow physiological distribution of fluids, permit thoracic compression at depth, heat the spinal cord, and regulate the oxygenation of the brain during the long breath-holding dives.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NO, located in sympathetic nerves, can be released as a co-transmitter in the peripheral autonomic system and induces vasodilator effects (Toda and Okamura, 2003). It is well known that Cetaceans have morphophysiological features that permit them to live in aquatic environment (Nagel et al, 1968;Vogl and Fisher, 1981;Ochrymowych and Lambertsen, 1984;Melnikov, 1997;Bombardi et al, 2010Bombardi et al, , 2011. In particular, during diving, blood is shifted to the huge retia mirabilia, to allow physiological distribution of fluids, permit thoracic compression at depth, heat the spinal cord, and regulate the oxygenation of the brain during the long breath-holding dives.…”
Section: Discussionmentioning
confidence: 99%
“…Direct neural control of retial arteries would allow rapid blood redistribution (Nagel et al, 1968), but although ample innervation runs in close proximity to dolphin and fin whale rete (Nagel et al, 1968;Ommanney, 1932), direct adrenergic connections have been shown to be poor in the rete of the narwhal (Vogl et al, 1981). Pfeiffer et al (Pfeiffer and Kinkead, 1990), studying nonthoracic retial arteries from the bowhead whale, Balaena mysticetus, came to a similar conclusion based on a number of morphological features including the observation of ganglia-like complexes in the media, but no diffuse neurons.…”
Section: Model Predictions Of Thoracic Pressurementioning
confidence: 99%
“…In our research, however, the high percentage ($50%) of SP-IR neurons reflects a previously unreported situation (Lawson, 1992;Willis and Coggeshall, 2004), possibly typical of the dolphin. Cetaceans have unique morphophysiological vascular features that reflect an extreme adaptation to the aquatic environment (Nagel et al, 1968;Vogl and Fisher, 1981;Ochrymowych and Lambertsen, 1984;Melnikov, 1997;Sedmera et al, 2003). In particular, the vascular system of cetaceans shows numerous retia mirabilia.…”
Section: Discussionmentioning
confidence: 99%